Simultaneous analysis of saturated and unsaturated fatty acids present in pequi fruits by capillary electrophoresis - Nery-Enes, Bárbara; Barra, Patrícia M. de Castro; Oliveira, Marcone A. L. de; Cardoso, Leandro de M.; Cesário, Cristiane do C.; Moreira, Ana V. B.; Pinheiro-Sant'Ana, Helena M.; Peluzio, Maria do C. G. (Química Nova, 2013)
In the current study, an alternative method has been proposed for simultaneous analysis of palmitic, stearic, oleic, linoleic, and linolenic acids by capillary zone electrophoresis (CZE) using indirect detection. The background electrolyte (BGE) used for the analysis of these fatty acids (FAs) consisted of 15.0 mmol L^−1 NaH2PO4/Na2HPO4 at pH 6.86, 4.0 mmol L^−1 SDBS, 8.3 mmol L^−1 Brij 35, 45% v/v acetonitrile (can), and 2.1% n-octanol. The FAs quantification of FAs was performed using a response factor approach, which provided a high analytical throughput for the real sample. The CZE method, which was applied successfully for the analysis of pequi pulp, has advantages such as short analysis time, absence of lipid fraction extraction and derivatization steps, and no significant difference in the 95% confidence intervals for FA quantification results, compared to the gas chromatography official method (AOCS Ce 1h-05).
O artigo não contém o resumo em português.
Keywords: Pequi fruit; Gas chromatography; Capillary zone electrophoresis